Transient Hypothyroidism in Premature Infants After Short-term Topical Iodine Exposure: An Avoidable Risk? - Jordan E. Pinsker; Krista McBayne; Mary Edwards; Kirk Jensen; David F. Crudo; Andrew J. Bauer (Pediatrics and Neonatology)
Studies in preterm infants have shown that prolonged treatment with topical iodine (multiple doses, often over multiple days) can transiently suppress thyroid function. However, it is uncertain if topical iodine exposure for very short periods of time can cause significant changes in thyroid function. We report two cases of transient hypothyroidism in preterm infants after short-term exposure to topical iodine during surgical preparation, and review their clinical and laboratory findings before and after iodine exposure. We conclude that premature infants are at risk of developing transient hypothyroidism in response to a single, short-term exposure to topical iodine, even in iodine-sufficient geographical areas. We advise monitoring of thyroid function in these infants after iodine exposure, as treatment with levothyroxine may be needed for a limited duration to prevent the sequelae of untreated hypothyroidism. Consideration of using alternative cleansing agents is also advised.